Essential Oils For Beginners : A Proven Guide For Essential Oils and Aromatherapy For Weight Loss, Stress Relief And A Better LIfe - Joy Sarah ([t.penerbit], 2015)
This book will teach you everything you need to know about aromatherapy and essential oils.